SU-8 microstructure for quasi-three-dimensional cell-based biosensing - Wang, Lina; Wu, Ze-Zhi; Xub, Bingqian; Zhaoc, Yiping; Kisaalita, William S. (Sensors and Actuators B: Chemical, 2009)
A quasi-three-dimensional (quasi-3-D) cell-based biosensor platform microfabricated from SU-8 has been developed and characterized. In this work, SH-SY5Y human neuroblastoma cells were integrated with SU-8 microfabricated microwells with diameters of 100μm. SH-SY5Y cells were differentiated with 1mM dibutyryl cAMP and 2.5μM 5-bromodeoxyuridine. Voltage-gated calcium channel (VGCC) function of SH-SY5Y cells cultured within the microwells (quasi-3-D) versus those cultured on the SU-8 planar substrates (2-D) was evaluated by confocal microscopy with a calcium fluorescent indicator, Calcium Green-1. In response to 50mM high K+ depolarization, cells in microwells were less responsive in terms of increase in intracellular Ca2+ in comparison to cells on 2-D substrates. This study shows that VGCC function of cells within SU-8 microwells was indeed different from that of cells on planar SU-8 surfaces, suggesting that SU-8 microstructure did affect SH-SY5Y cell differentiation with respect to VGCC function and that high-aspect-ratio microstructures are not merely “folded” 2-D structures. Furthermore, these results are consistent with previous 2-D/3-D comparative studies carried out in polymer scaffolds and support the hypothesis that cell calcium dynamics on 2-D substrates may be exaggerated. Overall, this work is supportive of SU-8 micropattern as a viable platform for engineering a quasi-3-D cell culture system for cell-based biosensing against drugs for VGCCs.